Hypervalent iodine(III)-induced methylene acetoxylation of 3-oxo-N-substituted butanamides - Liu, Wei-Bing; Chen, Cui; Zhang, Qing; Zhu, Zhi-Bo (Beilstein Journal of Organic Chemistry, 2011)
1-Carbamoyl-2-oxopropyl acetate derivatives were synthesized through an acetoxylation process to methylene with the aid of (diacetoxyiodo)benzene (DIB) as the oxidant. Not only mild reaction conditions, but also excellent yields and good substrate scope make the present protocol potentially useful in organic synthesis.
Keywords: 1-carbamoyl-2-oxopropyl acetate derivatives; C-hetero bond; (diacetoxyiodo)benzene; methylene acetoxylation